The Effectiveness of A Strategy Based on Positive Planning In Obtaining Fourth-Grade Literary Students’ Achievement In The Subject of History And Their Emotional Regulation (Journal of the College of Basic Education, 2025)
The current research aims to identify the effectiveness of a proposed strategy according to positive thinking in the achievement of fourth-grade literary students in the subject of history and their emotional regulation. The sample of the current research was determined by fourth-grade literary students affiliated with the Second Rusafa Education Schools in Baghdad Governorate for the academic year (2023-2024). Students of the literary quarter class at Saad bin Abi Waqqas School for Boys were chosen to be its students as a research sample intentionally. Two halls were chosen from a total of four halls of fourth-grade literary students, one of the two groups is experimental and the other is control. The sample amounted to (70) students, including (35) students in the experimental group and (35) students in the control group. The researcher rewarded the two research groups in variables (intelligence test, chronological age, emotional regulation). The achievement test was also prepared, as (35) paragraphs were formulated in line with the content of the material and behavioral purposes (cognitive, understanding, application), the emotional regulation test, as a test was prepared by the researcher, which is the emotional regulation, which consisted of (15) paragraphs, and the data were analyzed using the statistical program (SPSS.V.21) The results showed that the experimental group students who studied with the proposed strategy for positive thinking outperformed the group students who studied with the traditional method of emotional regulation. Based on the research results, the researcher recommends the need to pay attention to the positive thinking strategy in teaching history because of its positive effect in increasing emotional regulation among students. In order to verify the research objective, the researcher put forward the following urban hypothesis: -1- "There are no statistically significant differences at the level of (0.05) between the average score of the experimental group students who study according to the proposed strategy for positive thinking, and the score of the control group students who study with the traditional method in achievement."2- "There is no statistically significant difference at the level of (0.05) between the average score of the students of the experimental group who study with the strategy (positive thinking), and the average score of the students of the experimental group who study with the traditional method in emotional regulation." Keywords: Proposed strategy in positive thinking, emotional regulation, fourth grade literary students, history subject